Dampak pencabutan subsidi pupuk terhadap kinerja usaha tani dan efisiensi komoditas non-subsidi: studi kasus komoditas kentang dan wortel: The impact of fertilizer subsidy removal on farm performance and efficiency of non-subsidized commodities: a case study of potatoes and carrots commodities - Setyaningrum, Widyadhari Febriani; Sumedi; Yofa, Rangga Ditya (Analisis Kebijakan Pertanian, 2025)
The enactment of the Ministry of Agriculture Regulation Number 10/2022, which, among other things, allocates subsidized fertilizer only to nine commodities, marks a new milestone in the management of subsidized fertilizer. This study aims to analyze the responses of potato and carrot farmers who do not receive subsidized fertilizer allocations regarding input use, production, nominal and real input costs, and technical efficiency. The National Farmer Panel (Patanas) data from 2017 and 2023, conducted by the Center for Agricultural Socioeconomic and Policy Studies (ICASEPS), were used. The data were analyzed using quantitative descriptive methods. The study results show that in potato and carrot farming, there has been a decrease in subsidized fertilizer use between 98-100 percent and 59-200 percent, and a decrease in production of 31.78 percent and 7.0 percent, respectively. In nominal terms, potato farming costs in 2017 and 2023 were relatively similar, but in real terms, they decreased, especially for fertilizer. At the same time, in carrot farming, input costs in nominal terms increased significantly by 99.69. In real terms, almost all input costs increased, particularly land rent and fertilizer. The withdrawal of subsidized fertilizer allocation for potato farming led to reduced fertilizer use, whereas that for carrot farming was replaced by non-subsidized fertilizer. Potato and carrot productivity decreased by 31.78 percent and 59.81 percent, and technical efficiency decreased by 30.45 percent and 22.62 percent, respectively. The results of this study indicate that government policy has had a negative impact on horticultural farming, and thus, there is a need to improve the governance of subsidized fertilizer.
Keywords: production; subsidized fertilizer; technical efficiency; potatoes; carrot farming